Study of prebiotic properties from edible mushroom extraction - Sawangwan, Thornthan; Wansanit, Wanwipa; Pattani, Lalita; Noysang, Chanai (Agriculture and Natural Resources, 2018)
The prebiotic properties were investigated of seven edible mushrooms: Auricularia auricula-judae, Lentinus edodoes, Pleurotus citrinopileatus, Pleurotus djamor, Pleurotus ostreatus, Pleurotus ostreatus (Jacq.Fr.) Kummer and Pleurotus pulmonarius. All mushrooms were extracted using distilled water and ethanol at a ratio of 1:4 vol per volume, respectively, at 80 °C and shaken at 150 revolutions per minute for 1-4 hr before the total carbohydrates and total reducing sugar were determined. After 3 hr of extraction, P. ostreatus had the maximum yield of total carbohydrates (6.7325 ± 0.0261 mg/mL) and total reducing sugar (2.6737 ± 0.0027 mg/mL). Based on high performance liquid chromatography analysis, A. auriculajudae had the highest levels of galactose and maltrotriose (928.26 mM and 112.59 mM, respectively), while L. edodoes had a high lactulose level (229.64 mM). Each mushroom extract was supplemented in Man Rogosa Sharpe broth for cultivation of probiotic strains of L. acidophilus and L. plantarum. Next, the prebiotic properties were determined based on probiotic growth stimulation, pathogenic inhibition (against Bacillus cereus, Escherichia coli, Samonella Paratyphi and Stapphylococcus aureus) and gastrointestinal tolerance (in amylase, bile extract and HCl). High probiotic growth stimulation resulted for L. acidophilus cultured with L. edodoes extract (1.9779 ± 0.0032), and for L. plantarum cultured with P. pulmonarius extract (1.9702 ± 0.0072). The widest inhibition zone of S. Paratyphi in the culture of L. acidophilus was 1.1500 ± 0.0707 cm with P. ostreatus extract. The highest survival percentage for gastrointestinal tolerance of probiotics after incubation for 2 hr with HCl was 13.64% for P. djamor extract cultured in L. acidophilus.